Digitalisasi Marketing UMKM Sebagai Pendorong Peningkatan Ekonomi Masyarakat Desa Cikawung Kecamatan Pekuncen Kabupaten Banyumas - Pipin Sri Sudewi; Amin Budiastuti; Rosalina Anindya Sari Kartika; Susanti Budiastuti; Sri Hartati (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
Digitalization of MSME Marketing is a change from conventional to digital systems as an effort to increase the effectiveness and efficiency of business processes and MSME operations and make MSME business actors change their business management, especially in the field of marketing from conventional to modern practices. MSME stands for Micro, Small and Medium Enterprises, which is one of the models in trading activities, usually carried out by individuals or individuals with business entities that are smaller in scope. Cikawung Village as one of the villages where some of the people, apart from farming, are also MSME players, feels the need for digital technology for business continuity and economic improvement of the village community.